The composition of the lipid, protein and mineral fractions of quail breast meat obtained from wild and farmed specimens of Common quail (Coturnix coturnix) and farmed Japanese quail (Coturnix japonica domestica) - Quaresma, MAG (2022)
Research Areas: Agriculture ; Dairy & Animal Science